Improving childhood asthma outcomes in the United States : a blueprint for policy action - Lara, Marielena (RAND health, 2001)
An estimated 5 million U.S. children have asthma. Too many of these children are unnecessarily impaired. Much of the money spent on asthma is for high-cost health care services to treat acute periods of illness. Many asthma attacks could be avoided--and much suffering prevented and many medical costs saved--if more children received good-quality, ongoing asthma care and if the 11 policy recommendations presented in this report were implemented in a coordinated fashion. A national call to action, the policy recommendations span public and private interests and compel integration of public health activities across local, state, and federal levels. This report summarizes the findings of an effort funded by the Robert Wood Johnson Foundation as part of the Pediatric Asthma Initiative, whose purpose is to address current gaps in national childhood asthma care. It is the first national initiative that simultaneously addresses treatment, policy, and financing issues for children with asthma at the patient, provider, and institutional levels. The purpose of RAND's effort was to 1) identify a range of policy actions in both the public and private sectors that could improve childhood asthma outcomes nationwide; 2) select a subset of policies to create a blueprint for national policy in this area; 3) outline alternatives to implement these policies that build on prior efforts. The effort developed a comprehensive policy framework that maps the identified strategies to one overall policy objective: to promote the development and maintenance of "asthma-friendly" communities--communities in which children with asthma are swiftly diagnosed, receive appropriate and ongoing treatment, and are not exposed to environmental factors that exacerbate their condition. This report is intended as a working guide for coordinating the activities of both public and private organizations at the federal, state, and local community levels